2018
DOI: 10.1186/s13024-018-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Joint genome-wide association study of progressive supranuclear palsy identifies novel susceptibility loci and genetic correlation to neurodegenerative diseases

Abstract: BackgroundProgressive supranuclear palsy (PSP) is a rare neurodegenerative disease for which the genetic contribution is incompletely understood.MethodsWe conducted a joint analysis of 5,523,934 imputed SNPs in two newly-genotyped progressive supranuclear palsy cohorts, primarily derived from two clinical trials (Allon davunetide and NNIPPS riluzole trials in PSP) and a previously published genome-wide association study (GWAS), in total comprising 1646 cases and 10,662 controls of European ancestry.ResultsWe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
141
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 47 publications
9
141
1
Order By: Relevance
“…BBBIPPS used the same NNIPPS diagnostic criteria and was conducted in the same study centers in France. These patients were previously included as a subset of a GWAS in PSP that we had published …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BBBIPPS used the same NNIPPS diagnostic criteria and was conducted in the same study centers in France. These patients were previously included as a subset of a GWAS in PSP that we had published …”
Section: Methodsmentioning
confidence: 99%
“…NNIPPS and BBBIPPS recruited a well‐characterized cohort of patients with PSP. This cohort was also included in our previously reported joint‐analysis GWAS of PSP . Here, we performed genome‐wide association on this cohort alone to confirm genetic loci implicated in PSP and validate this clinical PSP cohort, comparing with previous GWASs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first study selected specific SNPs from the Höglinger GWAS and reassessed them in a cohort combining the original population and new definite PSP cases and controls . The second study combined the definite cases of the Höglinger GWAS with new cases with clinical PSP diagnosis and utilized a genotype imputation methodology . Both studies also reported new associations, the first with a nonsynonymous SNP in the SLCO1A2 gene and an intergenic SNP near DUSP10 , and the second study with an intronic SNP in the SLCO1A2 gene and an SNP associated with the RUNX2 gene.…”
Section: Psp: Milestones Of the Recent 10 Yearsmentioning
confidence: 99%
“…Both studies also reported new associations, the first with a nonsynonymous SNP in the SLCO1A2 gene and an intergenic SNP near DUSP10 , and the second study with an intronic SNP in the SLCO1A2 gene and an SNP associated with the RUNX2 gene. All the studies mentioned above have confirmed the contribution of the H1 haplotype in the risk of PSP and some have identified additional SNPs in the MAPT locus that independently influence this risk . Using a different approach, Jabbari and colleagues conducted a GWAS with genotype imputation comparing cases with RS versus cases with PSP‐P and PSP‐PGF.…”
Section: Psp: Milestones Of the Recent 10 Yearsmentioning
confidence: 99%